2009
DOI: 10.1002/marc.200800700
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly and Dynamics of Polypeptides

Abstract: This work highlights the results of recent efforts to understand the hierarchical self-assembly and dynamics of polypeptides with the aid of different NMR techniques, X-ray scattering, and dielectric spectroscopy. The concerted application of these techniques sheds light on the origin of the glass transition, the persistence of the α-helical peptide secondary motif, and the effects of topology and packing on the type and persistence of secondary structures. With respect to the freezing of the dynamics at the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 86 publications
2
60
0
2
Order By: Relevance
“…Cross‐polarization magic‐angle spinning (CPMAS) 13 C NMR spectroscopy was used to identify the β‐sheet content in the supramolecular copolymers. It is known for polypeptides in particular that the chemical shift of carbonyl carbon atoms obtained by CPMAS 13 C NMR spectroscopy strongly depends on the secondary structure and is, therefore, highly diagnostic 25. A freeze‐dried solution of 1:1 mixtures of co ‐ monomers 1 a and 1 b shows a chemical shift of δ =172±1 ppm for the carbonyl carbon atom (see Figure S3 in the Supporting Information), which is in excellent agreement with reported values for β‐sheet‐ordered oligoalanines, ‐lysines, and ‐glutamic acids 26.…”
mentioning
confidence: 99%
“…Cross‐polarization magic‐angle spinning (CPMAS) 13 C NMR spectroscopy was used to identify the β‐sheet content in the supramolecular copolymers. It is known for polypeptides in particular that the chemical shift of carbonyl carbon atoms obtained by CPMAS 13 C NMR spectroscopy strongly depends on the secondary structure and is, therefore, highly diagnostic 25. A freeze‐dried solution of 1:1 mixtures of co ‐ monomers 1 a and 1 b shows a chemical shift of δ =172±1 ppm for the carbonyl carbon atom (see Figure S3 in the Supporting Information), which is in excellent agreement with reported values for β‐sheet‐ordered oligoalanines, ‐lysines, and ‐glutamic acids 26.…”
mentioning
confidence: 99%
“…The concerted application of these techniques shed light onto the origin of the glass transition, the persistence of the a-helical peptide secondary motif and the effects of topology and packing on the type and persistence of secondary structures. 81 Protein function and applications often depend on these issues. Using poly(g-benzyl-L-glutamate), PBLG, as an example, it was shown that helices are objects of rather low persistence in the bulk as well as in concentrated solutions in helicogenic solvents.…”
Section: Self-assembly and Dynamics Of Polypeptidesmentioning
confidence: 99%
“…Sie lieferten Hintergründe des Glasübergangs, die Persistenz der a‐helikalen Sekundärstrukturen und den Einfluss von Topologie‐ und Packungseffekten auf Typ und Persistenz der Sekundärstrukturen. Ergänzend dazu beschrieb Brown die seit Kurzem möglichen Anwendungen neuer 1H, 2H, 13C, 15N und 17O‐Festkörper‐Kernspinresonanzmethoden (magic angle spinning nuclear magnetic resonance, MAS‐NMR) 58. Struktur und dynamische Prozesse, welche die Bulkeigenschaften polymerer und supramolekularer Systeme bestimmen, lassen sich so aufklären.…”
Section: Charakterisierung Und Modellierungunclassified